2005
DOI: 10.1007/s10589-005-3058-z
|View full text |Cite
|
Sign up to set email alerts
|

A Constraint Programming Approach to Extract the Maximum Number of Non-Overlapping Test Forms

Abstract: This paper introduces a novel approach for extracting the maximum number of non-overlapping test forms from a large collection of overlapping test sections assembled from a given item bank. The approach involves solving maximum set packing problems (MSPs). A branch-and-bound MSP algorithm is developed along with techniques adapted from constraint programming to estimate lower and upper bounds on the optimal MSP solution. The algorithm is general and can be applied in other applications including combinatorial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 18 publications
1
12
0
Order By: Relevance
“…Our complexity results follow the line of previous works (like Belov & Armstrong, 2006;Nguyen & Fong, 2013;Ishii et al, 2014) in which other formula-800 tions of the test assembly design problem were identified as classical strongly NP-hard combinatorial optimization problems. Our approach differs when we consider the resolution considerations, as Belov & Armstrong (2006) ;Nguyen & Fong (2013); Ishii et al (2014) apply classical algorithms of the identified optimization problem to the resolution of the test design problem, while our Bin Packing-based formulation significantly differs from the classical problem, thus forcing us to develop specially tailored procedures for its resolution.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Our complexity results follow the line of previous works (like Belov & Armstrong, 2006;Nguyen & Fong, 2013;Ishii et al, 2014) in which other formula-800 tions of the test assembly design problem were identified as classical strongly NP-hard combinatorial optimization problems. Our approach differs when we consider the resolution considerations, as Belov & Armstrong (2006) ;Nguyen & Fong (2013); Ishii et al (2014) apply classical algorithms of the identified optimization problem to the resolution of the test design problem, while our Bin Packing-based formulation significantly differs from the classical problem, thus forcing us to develop specially tailored procedures for its resolution.…”
Section: Discussionsupporting
confidence: 83%
“…Our approach differs when we consider the resolution considerations, as Belov & Armstrong (2006) ;Nguyen & Fong (2013); Ishii et al (2014) apply classical algorithms of the identified optimization problem to the resolution of the test design problem, while our Bin Packing-based formulation significantly differs from the classical problem, thus forcing us to develop specially tailored procedures for its resolution.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, alternative methods have been developed that greatly outperform sequential assembly by utilizing properties of the feasible set. Belov and Armstrong (2006) suggested a set packing approach. They assembled multiple nonoverlapping tests in two stages:…”
Section: Extracting Multiple Nonoverlapping (Or Partially Overlappingmentioning
confidence: 99%
“…Since each item from the pool can be used in multiple combinations satisfying test specifications, tests from the feasible set can overlap each other. Certain subsets of the feasible set play an important role in practice, in particular, subsets where tests do not overlap each other (van der Linden, 2005a;Belov & Armstrong, 2005a;Belov & Armstrong, 2006). If the test specifications describe m > 1 non-overlapping tests (van der Linden, Ariel, & Veldkamp, 2006), we interpret them as one lengthy test and the solution to the corresponding system of inequalities is a 0-1 vector of size n = mn.…”
Section: Introductionmentioning
confidence: 99%